Hubungan antara Persepsi Manajemen Lini terhadap Turnover di Manajemen Puncak dengan Komitmen Organisasi - Susatyo Yuwono; Yadi Purwanto; Ade Kurniawan (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This research’s aim is to find the correlation between line management’s perception about top management’s turnover and organizational commitment. The hypotesis is there is a correlation between line management’s perception about top management’s turnover and organizational commitment. Population, as subject, are 37 line management’s of PT Krakatau Engineering,. Data gathered by questionnaires: line management’s perception about top management’s turnover, and organizational commitment.The analysis by product moment techniques, and the results shows correlation index (r) = 0,584, p < 0,01. It means there is a positive very significant correlation between line management’s perception about top management’s turnover and organizational commitment. Keyword: perception on turnover, organizational commitment